The business of digital television - Forrester, Chris (Focal Press, 2000)
Essential reading for anyone involved in broadcasting. The Business of Digital Television presents an overview or the digital television industry. Chris Forrester examines the key technologies and developments of the marketplace, with comments on the future from leading industry experts. Written in an accessible style for the non-engineer, Forrester covers the issues that are most pertinent to strategic direction, providing, broadcasting professionals with essential facts, data and commentary in one single source. You will: Discover trends in digital TV technology Gain knowledge about the inte.